Question
upstudy study bank question image url

Using the Quotient Rule In Exercises 7-12, use the Quotient Rule to find the derivative of the function. \( \begin{array}{ll}\text { 7. } f(x)=\frac{x}{x^{2}+1} & \text { 8. } g(t)=\frac{3 t^{2}-1}{2 t+5} \\ \text { 9. } h(x)=\frac{\sqrt{x}}{x^{2}+1} & \text { 10. } f(x)=\frac{x^{2}}{2 \sqrt{x}+1} \\ \text { 11. } g(x)=\frac{\sin x}{x^{2}} & \text { 12. } f(t)=\frac{\cos t}{t^{3}}\end{array} \)

Ask by Mejia Knight. in the United States
Feb 26,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

Here are the derivatives using the Quotient Rule: 7. \( f'(x) = \frac{1 - x^2}{(x^2 + 1)^2} \) 8. \( g'(t) = \frac{6t^2 + 30t + 2}{(2t + 5)^2} \) 9. \( h'(x) = \frac{1 - 3x^2}{2\sqrt{x} \cdot (x^2 + 1)^2} \) 10. \( f'(x) = \frac{x(3\sqrt{x} + 2)}{(2\sqrt{x} + 1)^2} \) 11. \( g'(x) = \frac{x \cos x - 2 \sin x}{x^3} \) 12. \( f'(t) = \frac{-(t \sin t + 3 \cos t)}{t^4} \) Any equivalent algebraic form is correct.

Solution

We are given functions written as quotients. Recall that the Quotient Rule states that if   F(x) = U(x)/V(x), then   F ′(x) = [V(x)·U ′(x) − U(x)·V ′(x)]⁄[V(x)]². Below are the step‐by‐step calculations for Exercises 7–12. ───────────────────────────── 1. Exercise 7:   f(x) = x⁄(x² + 1) Here, U(x) = x with U ′(x) = 1, and V(x) = x² + 1 with V ′(x) = 2x. Applying the Quotient Rule:   f ′(x) = [(x² + 1)(1) − x(2x)]⁄(x² + 1)²        = [x² + 1 − 2x²]⁄(x² + 1)²        = (1 − x²)⁄(x² + 1)² ───────────────────────────── 2. Exercise 8:   g(t) = (3t² − 1)⁄(2t + 5) Here, U(t) = 3t² − 1 with U ′(t) = 6t, and V(t) = 2t + 5 with V ′(t) = 2. Then,   g ′(t) = [(2t + 5)(6t) − (3t² − 1)(2)]⁄(2t + 5)²        = [12t² + 30t − 6t² + 2]⁄(2t + 5)²        = (6t² + 30t + 2)⁄(2t + 5)² ───────────────────────────── 3. Exercise 9:   h(x) = √x⁄(x² + 1)     (write √x as x^(1/2)) Let U(x) = x^(1/2) so that U ′(x) = (1)/(2x^(1/2)) and V(x) = x² + 1 so that V ′(x) = 2x. Thus,   h ′(x) = [(x² + 1)·(1/(2√x)) − √x·(2x)]⁄(x² + 1)² Now, simplify the numerator:   = [ (x² + 1)/(2√x) − 2x√x ]⁄(x² + 1)² Recognize that 2x√x = 2x^(3/2). To combine terms, find a common denominator (2√x):   = [ (x² + 1 − 4x²)/(2√x) ]⁄(x² + 1)²   = (1 − 3x²)⁄[2√x·(x² + 1)²] ───────────────────────────── 4. Exercise 10:   f(x) = x²⁄(2√x + 1)     (write √x as x^(1/2)) Let U(x) = x² so that U ′(x) = 2x, and let V(x) = 2x^(1/2) + 1. Differentiate V(x): since the derivative of 2x^(1/2) is 2·(1/2)x^(–1/2) = x^(–1/2), we have V ′(x) = 1/√x. Now apply the Quotient Rule:   f ′(x) = [(2√x + 1)(2x) − x²·(1/√x)]⁄(2√x + 1)² Simplify the numerator:   (2√x + 1)(2x) = 4x√x + 2x  and  x²·(1/√x) = x^(3/2) Thus,   Numerator = 4x^(3/2) + 2x − x^(3/2) = 3x^(3/2) + 2x We can factor an x:   = x(3√x + 2) So,   f ′(x) = [x(3√x + 2)]⁄(2√x + 1)² ───────────────────────────── 5. Exercise 11:   g(x) = sin x⁄x² Let U(x) = sin x so that U ′(x) = cos x, and V(x) = x² so that V ′(x) = 2x. Then,   g ′(x) = [x²·cos x − sin x·(2x)]⁄(x²)²        = [x² cos x − 2x sin x]⁄x⁴ Factor an x from the numerator:   = x(x cos x − 2 sin x)⁄x⁴ = (x cos x − 2 sin x)⁄x³ ───────────────────────────── 6. Exercise 12:   f(t) = cos t⁄t³ Here, U(t) = cos t with U ′(t) = −sin t, and V(t) = t³ with V ′(t) = 3t². Using the Quotient Rule:   f ′(t) = [t³·(−sin t) − cos t·(3t²)]⁄(t³)²        = [−t³ sin t − 3t² cos t]⁄t⁶ Factor t² from the numerator:   = −t² (t sin t + 3 cos t)⁄t⁶ = −(t sin t + 3 cos t)⁄t⁴ ───────────────────────────── Final Answers: 7. f ′(x) = (1 − x²)⁄(x² + 1)² 8. g ′(t) = (6t² + 30t + 2)⁄(2t + 5)² 9. h ′(x) = (1 − 3x²)⁄[2√x · (x² + 1)²] 10. f ′(x) = [x(3√x + 2)]⁄(2√x + 1)² 11. g ′(x) = (x cos x − 2 sin x)⁄x³ 12. f ′(t) = −(t sin t + 3 cos t)⁄t⁴ Any answer that is algebraically equivalent to these is correct.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Bonus Knowledge

To find the derivative of \( f(x) = \frac{x}{x^2 + 1} \) using the Quotient Rule, we first identify the numerator and the denominator: \( u = x \) and \( v = x^2 + 1 \). The Quotient Rule states that \( f'(x) = \frac{u'v - uv'}{v^2} \). Here, \( u' = 1 \) and \( v' = 2x \). Plugging in these values gives: \[ f'(x) = \frac{(1)(x^2 + 1) - (x)(2x)}{(x^2 + 1)^2} = \frac{x^2 + 1 - 2x^2}{(x^2 + 1)^2} = \frac{1 - x^2}{(x^2 + 1)^2}. \] Now, for \( g(t) = \frac{3t^2 - 1}{2t + 5} \), we again apply the Quotient Rule where \( u = 3t^2 - 1 \) and \( v = 2t + 5 \). We find \( u' = 6t \) and \( v' = 2 \). Therefore: \[ g'(t) = \frac{(6t)(2t + 5) - (3t^2 - 1)(2)}{(2t + 5)^2} = \frac{12t^2 + 30t - (6t^2 - 2)}{(2t + 5)^2} = \frac{6t^2 + 30t + 2}{(2t + 5)^2}. \] Use similar steps for the other functions. Just remember to identify the numerator and denominator clearly, take their derivatives, and apply the Quotient Rule formula! Happy differentiating!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy